Evaluation of P. moriformis oil and its blends with diesel fuel as promising contributors to transportation energy. (15th December 2019) - Raslavičius, Laurencas; Felneris, Mantas; Pukalskas, Saugirdas; Rimkus, Alfredas; Melaika, Mindaugas
Abstract: An extensive experimental study was conducted on the 1Z-type CI engine that was running on low, average and high load modes at n  = 2000 rpm and used diesel fuel, P. moriformis microalgal oil (PMO100), and their 30% and 70% blends (PMO30, PMO70). Variation of five different parameters of the engine's operational performance (BSFC, net efficiency, air mass flow, exhaust gas temperature, air-fuel equivalence ratio) and emissions of five chemical compounds (smoke, NOx, HC, CO2, O2 ) were established. The aforementioned parameters were repeatedly assessed for the engine running at low load conditions, with the advancement or retardation of the start of fuel injection timing ( SOI ) every 2° of the crankshaft rotation angle from −16° to +4° relative to TDC. The test results revealed that PMO100, PMO30/D70, and PMO70/D30 are more or less equally sensitive to key engine parameters, compared to diesel if proper regulation of SOI is applied. In order to explain the ongoing thermochemical processes within engine cylinders and to support the experimental findings, in-cylinder pressure, in-cylinder pressure rise rate, in-cylinder temperature, mass fraction burnt, in-cylinder temperature rise rate and in-cylinder heat release rate were assesed by using AVL BOOST software that indicated good agreement between simulation and experimental results. Highlights: This is the article on diesel engine performance on P. moriformis oil. We compared P. moriformis oil to fossil diesel using 10 different parameters. Various start of injection ( SOI ) angles relative to TDC were investigated. We established a specific interval of SOI for successful operation of an engine. P. moriformis oil is the promising contributor to increased transportation energy use.